Diagnosis and Management of Daptomycin-Induced Acute Eosinophilic Pneumonia: A Case Report - Fawzy Elbarbry; Kate Farthing; Shannon Arguello (University of Minnesota Libraries Publishing, 2024)
Daptomycin is a cyclic lipopeptide antibiotic that is indicated for the treatment of complicated skin infections and bacteremia caused by gram positive organisms. Acute eosinophilic pneumonia (AEP) is a rare, but serious adverse effect of daptomycin and caused by accumulation of eosinophils in the lung tissues, and can lead to respiratory failure. Early diagnosis and management of this condition is crucial to avoid severe complications, including death. Herein, we report a case of an elderly man who presented with signs and symptoms of AEP within two weeks of initiation of daptomycin for the treatment of MRSA bacteremia. The patient showed significant clinical improvement and decline in eosinophils upon discontinuation of daptomycin and starting a 5-day steroid course. Acute eosinophilic pneumonia should be kept in mind as a possible, although rare, adverse effect of daptomycin. Early recognition can be established through typical symptoms, eosinophilia, and chest X-ray showing pulmonary infiltrate. Rapid discontinuation of daptomycin with/without steroid therapy and supportive care usually results in significant clinical recover.